Orthopaedic Physician Attire Influences Patient Perceptions in an Urban Inpatient Setting. Issue 9 (September 2019) - Jennings, John D.; Pinninti, Angelica; Kakalecik, Jaquelyn; Ramsey, Frederick V.; Haydel, Christopher
Abstract: Background: Prior research suggests that physician attire has an important effect on patient perceptions, and can influence the patient-physician relationship. Previous studies have established the effect of specialty, location, and setting on patient preferences for physician attire, and the importance of these preferences and perceptions on both the physician-patient relationship and first impressions. To date, no studies have examined the influence of attire in the inpatient orthopaedic surgery setting on these perceptions. Questions/purposes: (1) Do differences in orthopaedic physician attire influence patient confidence in their surgeon, perception of trustworthiness, safety, how caring their physician is, how smart their surgeon is, how well the surgery would go, and how willing they are to discuss personal information with the surgeon? (2) Do patients perceive physicians who are men and women differently with respect to those endpoints? Methods: Ninety-three of 110 patients undergoing orthopaedic surgery at an urban academic medical center participated in a three-part survey. In the first part, each patient was randomly presented 10 images of both men and women surgeons, each dressed in five different outfits: business attire (BA), a white coat over business attire (WB), scrubs alone (SA), a white coat over scrubs (WS), and casual attire (CA). Respondents rated each image on a five-point Likert scale regarding how confident, trustworthy, safe, caring, and smart the surgeon appeared, how well the surgery would go, and the patient's willingness to discuss personal information with the surgeon. In the second part, the respondent ranked all images, by gender, from the most to least confident based on attire. Results: Pair-wise comparisons for women surgeons demonstrated no difference in patient preference between white coat over business attire compared with white coat over scrubs or scrubs alone, though each was preferable to business attire and casual attire (WS versus WB: mean difference [MD], 0.1 ± 0.6; 95% CI, 0.0–0.2; p = 1.0; WS versus SA: MD, 0.2 ± 0.7; 95% CI, 0–0.3; p = 0.7; WB versus SA: 0.1 ± 0.9; 95% CI, -0.1 to 0.2; p = 1.0). The same results were found when rating the surgeon's perceived intelligence, skill, trust, confidentiality, caring, and safety. In the pair-wise comparisons for male surgeons, white coat over scrubs was not preferred to white coat over business attire, scrubs alone, or business attire (WS versus WB: MD, -0.1 ± 0.6; 95% CI, 0–0.1; p = 1.0; WS versus SA: MD, 0 ± 0.4; 95% CI, -0.2 to 0; p = 1.0; WS versus BA: MD, 0.2 ± 0.8; 95% CI, 0–0.4; p = 0.6). WB and SA were not different (MD, 0.0 ± 0.6; 95% CI, -0.1 to 0.2; p = 1.0), though both were preferred to BA and CA (WB versus BA: MD, 0.3 ± 0.8; 95% CI, 0.1–0.5; p = 0.02; WB versus CA: 1.0 ± 1.0; 95% CI, 0.8–1.2; p < 0.01). We found no difference between SA and BA (MD, 0.3 ± 0.7; 95% CI, 0.1–0.4; p = 0.06). We found that each was preferred to CA (SA versus CA: 0.9 ± 1.0; 95% CI, 0.7–1.2; p < 0.01; BA versus CA: 0.7 ± 1.0; 95% CI, 0.5–0.9; p < 0.01), with similar results in all other categories. When asked to rank all types of attire, patients preferred WS or WB for both men and women surgeons, followed by SA, BA, and CA. Conclusions: Similar to findings in the outpatient orthopaedic setting, in the inpatient setting, we found patients had a moderate overall preference for physicians wearing a white coat, either over scrubs or business attire, and, to some extent, scrubs alone. Respondents did not show any difference in preference based on the gender of the pictured surgeon. For men and women orthopaedic surgeons in the urban inpatient setting, stereotypical physician's attire such as a white coat over either scrubs or business attire, or even scrubs alone may improve numerous components of the patient-physician relationship and should therefore be strongly considered to enhance overall patient care. Level of Evidence: Level II, therapeutic study.